Drugs & life - Avis, Harry (WCB/McGraw-Hill, 1999)
This updated edition takes a non-judgemental approach to drugs, provides facts about drugs and their effects and allows students to make their own decisions about drug abuse. It offers expanded coverage of drugs and the law, and looks at alcohol, stimulants, hallucinogens, inhalants and narcotics